Two million years of environmental change: a case study from Wonderwerk Cave, Northern Cape, South Africa - Ecker, M (2015)
The arid interior of South Africa lacks long, continuous and well-dated climate and environmental proxy records that can be compared with cultural sequences and with broader global climate records. This thesis develops the first substantial terrestrial environmental sequence for the interior of southern Africa at the site of Wonderwerk Cave, spanning two million years of prehistory. Changes in vegetation and humidity over time were investigated by means of carbon and oxygen stable isotope analysis on fossil herbivore enamel and ostrich eggshell, creating two independent proxy datasets. The Holocene record was used as a baseline for comparing the Pleistocene sequence, but required chronological tightening. Therefore, nine new radiocarbon dates were obtained, and calibrated and modelled with existing dates to provide a firmer chronology. The ostrich eggshell isotope record suggests arid but variable conditions, with distinct phases of increased humidity in the Early Pleistocene and mid-Holocene. Enamel stable isotope results show clear differences in local resource availability between the Early and Mid-Pleistocene, and then between the Pleistocene and Holocene, with an overall trend of increasing aridity. In particular, the onset of dietary specialisation in grazers at 0.8Ma is linked to expanding C4 grasslands. Aridity was not the driver behind the increase in C4 grasses, but changing pCO2 levels at the Mid Pleistocene transition were identified as a possible key factor. The presence of C3 and C4 grasses in the Early Pleistocene, when compared to the domination of C4 grasses today, was fostered by reduced rainfall seasonality. Regional independent developments have to be considered, as other regions in South and East Africa show C4 dominated diets in herbivores at earlier times than at Wonderwerk Cave. In the Holocene, higher temporal resolution indicates phases of environmental change coinciding with changes in the cultural record.